Photonics for the virtualization of cultural heritage - Morita, María Mercedes (2023)
This work is a brief review of the state-of-the-art of photonics applications for the virtualization of cultural heritage, focusing mainly on 3D recording and digitization techniques, virtual reality and augmented reality.We show some LALFI-CIOp's contributions: the improvement of the resolution and accuracy of 3D reconstructions by using laser speckle and the combination of different imaging techniques, such as digital photogrammetry and Reflectance Transformation imaging; the development of low-cost systems to be used by museums; and virtual and augmented reality applications for dissemination of cultural heritage.Finally, we discuss an experience of transferring 3D digitization technology to several museums and cultural heritage institutions in Argentina and we propose an approach to extend the use of photonics in this field.